Pelatihan Bahasa Inggris bagi Guru TK Negeri dan Pos PAUD Kota Batam - Sulastri Manurung; Dewi Yana; Adam Adam; Juwita Boneka Sinaga (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
English is not included as a compulsory subject for Elementary School and young learners. However, most kindergartens and private primary schools in Batam, teach and use English intensively. It is different from the case of most state Kindergartens and in which teaching and learning English is very limited. This is also due to lack of knowledge and skills of teachers who teach in Kindergartens so teaching learning English for kindergarten students is difficult to apply. Based on the problem above, the lecturers team of English Department University of Riau Kepulauan provides English language training for teachers at Kindergartens Batam. The team collaborate with the Education Officer for PAUD and PNF Batam to choose and send delegation from each Kindergarten and Pos PAUD to participate in the training. After going through intensive training for 30 meetings, the trainees showed an improvement in English especially to deliver the teaching material for young learners which was integrated with some relevant and suitable teaching activities for young learners.